2000
DOI: 10.1089/10430340050015446
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses against Replication-Deficient Adenovirus Inhibit Ovalbumin-Specific Allergic Reactions in Mice

Abstract: Replication-deficient adenovirus vector (Ad) is one of the most efficient gene transfer vehicles for human gene therapy. However, Ad is antigenic, known to evoke prominent inflammatory responses in vivo, and there are concerns that using Ad in patients with immune-mediated disorders (allergy and autoimmune diseases) may affect the status of the diseases. To evaluate this concept in a manner close to clinical scenarios, a mouse model of airway eosinophilic inflammation was developed by administering intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…[25][26][27]43 It has been demonstrated that replicationdefective adenovirus without transgene could inhibit eosinophilic inflammation in the airway of OVA-sensitized mice. 25,44 Furthermore, administration of adenovirus expressing Th1-related cytokines (such as IL-12, IL-18 and IFN-g) reduced AHR and lung inflammation. 26,27 As another strategy in addition to Th1/Th2 modulation, we demonstrated that administration of AdFasL to OVA-sensitized mice reduced AHR and lung eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27]43 It has been demonstrated that replicationdefective adenovirus without transgene could inhibit eosinophilic inflammation in the airway of OVA-sensitized mice. 25,44 Furthermore, administration of adenovirus expressing Th1-related cytokines (such as IL-12, IL-18 and IFN-g) reduced AHR and lung inflammation. 26,27 As another strategy in addition to Th1/Th2 modulation, we demonstrated that administration of AdFasL to OVA-sensitized mice reduced AHR and lung eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Previous studies have shown that administrations of adenovirusmediated IL-12, IL-18, or IFN-g attenuate established allergen-induced airway inflammation and AHR. 26,27 Furthermore, introduction of this nonreplicanting adenovirus into murine lungs does not induce an inflammatory response in the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…47 The human IL-13R 2 chain cDNA fragment was inserted into the NotI site of shuttle plasmid pCMV-SV2þ, 48 which contains a portion of the adenovirus type 5 (Ad5) genome and the CMV early promoter/enhancer. The shuttle plasmid carrying the expression cassette of IL-13R 2 chain instead of the Ad5 E1 region and adenoviral genomic plasmid pJM17 (Microbix Biosystems, Toronto, Canada) containing the Ad5 genome with E1 and E3 deletions were cotransfected into 293 cells using the CalciumPhosphate Transfection System (Life Technologies, Grand Island, NY).…”
Section: Construction Of Replication-defective De1de3 Adenoviral Vectormentioning
confidence: 99%
“…Successful inhibition seems to depend on the immunization protocol used for priming mice. Suzuki et al 41 demonstrated that intranasal instillation of Ad after two sensitizing intraperitoneal injections with OVA lead to decreased IgE Ab production. In contrast, after subsequent aerosol challenge the IgE Ab titers were not significantly different from those of untreated control mice, although profound effects on eosinophil infiltration in the airways and local cytokine production were observed.…”
Section: Figure 6 Production Of ␤Gal-specific Antibodies After Therapmentioning
confidence: 99%